The evolution of wage statistics (Ellis, 1892)
Repr. from Quarterly Journal of Economics for Jan., 1892. Facsimile reprint: New York, Arno Press & The New York Times, 1970. (American labor. From conspiracy to collective bargaining. Advisory editors: L. Stein and Ph. Taft). In: Wages, hours, and strikes: ...